2017
DOI: 10.1103/physreva.96.022317
|View full text |Cite
|
Sign up to set email alerts
|

High-dimensional decoy-state quantum key distribution over multicore telecommunication fibers

Abstract: Multiplexing is a strategy to augment the transmission capacity of a communication system. It consists of combining multiple signals over the same data channel and it has been very successful in classical communications. However, the use of enhanced channels has only reached limited practicality in quantum communications (QC) as it requires the complex manipulation of quantum systems of higher dimensions. Considerable effort is being made towards QC using high-dimensional quantum systems encoded into the trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 51 publications
0
101
0
Order By: Relevance
“…As an example, high-speed classical communication at 10.16 Pbit s −1 has been demonstrated thanks to SDM combined with dense wavelength division multiplexing, polarization modulation and advanced coding [29]. Likewise, both multicore and few-mode fibres have been exploited for encoding and transmitting high-dimensional (Hi-D) quantum states [30][31][32].In particular, the cores or the modes of these special fibres have been used to increase the dimensionality of the Hilbert space, thus allowing higher photon information efficiency. Although Hi-D quantum states are suitable for high rate quantum communications, in specific channel conditions (low noise channel), it was experimentally demonstrated that SDM is suitable for very high rate secure communications [33].…”
Section: Resultsmentioning
confidence: 99%
“…As an example, high-speed classical communication at 10.16 Pbit s −1 has been demonstrated thanks to SDM combined with dense wavelength division multiplexing, polarization modulation and advanced coding [29]. Likewise, both multicore and few-mode fibres have been exploited for encoding and transmitting high-dimensional (Hi-D) quantum states [30][31][32].In particular, the cores or the modes of these special fibres have been used to increase the dimensionality of the Hilbert space, thus allowing higher photon information efficiency. Although Hi-D quantum states are suitable for high rate quantum communications, in specific channel conditions (low noise channel), it was experimentally demonstrated that SDM is suitable for very high rate secure communications [33].…”
Section: Resultsmentioning
confidence: 99%
“…Multicore fibers -Multicore fibers present wellperformant characteristics: they offer low losses (comparable with the standard single-mode fibers) and low cross-talk between cores (fundamental for reliable transmission of the qudits) [161]. Previous experiments already demonstrated the capability of transferring spatial modes of light with high-fidelity up to a dimension equal to four [162][163][164]. In particular, Y. Ding and coauthors used two silicon photonic platforms, connected by a 3 m MCF, for preparing and measuring the quantum states [162], as reported in Figure 8.…”
Section: Fiber-based Linksmentioning
confidence: 99%
“…loop phase stabilization system can be implemented for a longer transmission distance, as reported in. 35 In order to avoid influence by polarization drift, two different strategies can be used. Firstly, a two dimensional grating coupler associated with an MZI 36 can be used to couple with the cores of the MCF, so that the polarization for each core can be tuned independently.…”
Section: Discussionmentioning
confidence: 99%